Learning and collaboration technologies : design, development and technological innovation : 5th International Conference, LCT 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: design, development and technological innovation : 5th International Conference, LCT 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I (2018) - Unknown
No abstract available